Analyzing the Influence of Brand Ambassadors, Promotion, and Viral Marketing on Purchase Decisions for a Snack Brand - Dwi Hari Laksana; Yuli Liestyana; Nursabilla Marbun (AIBPM Publisher, 2025)
This study analyzes the effect of brand ambassadors, promotion, and viral marketing on purchase decisions of Tos Tos, a brand of tortilla chips snack. This study uses primary data. This study uses quantitative research with a population of NCT Dream fans in Indonesia. The sample taken in this study consisted of 105 respondents using a non-probability sampling method with a purposive sampling technique. The study used a questionnaire. The results of this study found that brand ambassadors, promotions, and viral marketing together have a significant effect on the decision to purchase Tos Tos snack. Brand ambassadors affect the decision to purchase Tos Tos snack. Promotion affects the decision to purchase Tos Tos snack. Viral marketing affects the decision to purchase Tos Tos snack. The researcher suggests that the Tos Tos snack company can maintain the number of advertisements on social media, the quality of message delivery, the reach of promotions, prize offers, and special offers offered. When viewed from the average promotion indicator, the special offer indicator has the lowest value, so the company needs to re-evaluate what special offers should be given to consumers. Consumers, when making purchasing decisions, will consider who advertises the product. The results of the research show that the promotion of the Tos Tos snack is very attractive to NCT Dream fans.